PERANAN PEMERINTAH DESA TERHADAP PENGELOLAAN BADAN USAHA MILIK DESA BINA BARU KACAMATAN KULO KABUPATEN SIDENRENG RAPPANG - Dedi Sudirman; Monalisa Ibrahim; Erfina Erfina (JIA: Jurnal Ilmiah Administrasi, 2021)
This study aims to determine the village government about the management of village-owned enterprises in the village of Bina Baru Kulo District, Sidenreng Rappang Regency. The population in this study were 266 heads of families in Bina Baru Village, Kulo District, Sidenreng Rappang Regency. This study uses the Slovin formula to a sample of 73 people based on data with incidental sampling techniques. Quantitative descriptive is the type of research used by this research. This research uses data collection techniques, namely observation, questionnaires, interviews and literature study. The data analysis technique used is the assistance of the IBM SPSS statistic 21.0 program. The results of this study indicate that the role of the village government is 48.9% less good. Management of Village-Owned Enterprises in Bina Baru Village, Kulo District, Sidenreng Rappang Regency 47.9% Poor Role of Village Government "Influential / Important" on Village-Owned Business Management in Bina Baru Village, Kulo District, Sidenreng Rappang District with t table t table value (4,980> 1, 66660) with a percentage of influence of 50.9% is not good, so that the role of the village government in the management of village-owned enterprises in Bina Baru Village, Kulo District, Sidenreng Rappang District has not been effective.